Recycling of bottom ash derived from combustion of cattle manure and its adsorption behaviors for Cd(II), Cu(II), Pb(II), and Ni(II) - Hong, Seung Hee; Shin, Myung Chul; Lee, Jechan; Lee, Chang Gu; Song, Dae Sung; Um, Byung Hwan; Park, Seong Jik (Environmental Science and Pollution Research, 2021)
Bottom ash generated by the combustion of cattle manure (BA-CCM) was investigated as an adsorbent for the removal of heavy metals such as Cd(II), Cu(II), Pb(II), and Ni(II) from aqueous solutions. When cattle manure was used as fuel, the thermal efficiency of the boiler was 88.7%, and the CO and CO2 concentrations in the exhaust gas were 2.3 ppm and 12.1%, respectively. The percentage of remaining solids was 31 wt.% after combustion at 900 °C. X-ray fluorescence analyses showed that the elemental composition of the BA-CCM was mainly CaO (43.3%), SiO2 (15.8%), CO2 (13.0%), and P2O5 (10.3%). The kinetic adsorption of Cd(II), Cu(II), Pb(II), and Ni(II) by BA-CCM reached equilibrium after 12 h, and the pseudo-second-order model fitted the experimental data well. The maximum amount of Cd(II), Cu(II), Pb(II), and Ni(II) adsorbed by the bottom ash was 5.4, 72.6, 88.2, and 24.6 mg/g, respectively. The equilibrium adsorption of metals onto BA-CCM was well-described by the Freundlich model. Thermodynamic analysis showed that the adsorption onto the bottom ash was endothermic and that the Gibbs free energy decreased as the temperature increased. The presence of cations such as Na+, Ca2+, and Al3+ was found to reduce the amount of metals adsorbed onto the BA-CCM, and Cd(II) adsorption was found to be more dependent on ionic strength than adsorption of Cu(II), Pb(II), and Ni(II). This study demonstrates the feasibility of producing heat energy by burning cattle manure and removing heavy metals from aqueous solutions using the generated bottom ash as an adsorbent.
Keywords: Adsorption; Animals; Cadmium; Cattle; Coal Ash; Hydrogen-Ion Concentration; Kinetics; Lead; Manure; Metals, Heavy; Silicon Dioxide; Adsorption; Bottom ash; Cattle manure; Combustion; Heavy metals; Recycling